7 to 13-year-old students' conceptual understanding of plant nutrition: should we be concerned about elementary teachers' instruction?. Issue 2 (15th March 2021) - Barrutia, Oihana; Díez, José Ramón
ABSTRACT: Plant nutrition is a complex subject at any educational level therefore, identification of student's ideas regarding this scientific concept is important in order to define the best instructional learning method. In this study, we conduct a cross-age comparison of the conceptual understanding of compulsory students and prospective elementary teachers about plant nutrition based on their drawings and explanations. It is observed that students' plant drawings are more accurate with age, including more plant structures involved in plant nutrition, while the presence of anthropocentric ideas in their responses decreases accordingly. However, the results show that, although knowledge about plant nutrition is acquired progressively with age through compulsory education, students do not completely understand plant nutrition-related processes, and more worryingly, this knowledge does not significantly improve from secondary to university levels. Moreover, even though the oldest students use more scientific terms in their explanations, they also nurture conceptual errors. This is cause for concern in the case of pre-service teachers, since they can transmit these misconceptions to their future elementary students. The current study reveals that plant nutrition (including photosynthesis) remains a difficult subject even at different educational stages, and that proper training imparted to elementary teachers can be crucial for a better understanding of this issue from early school years.